Role of ICTs in Increasing Agricultural Production as Perceived by the Coastal Farmers - Billah, Md Maruf; Hossain, Mohhamad Soliman; Ahmed, Tanvir; Karim, Md Riyajuddin; Hasan, Naymul (South Asian Journal of Agriculture, 2019)
The study was conducted to know the role of ICTs in increasing agricultural production perceived by the coastal farmers of southern Bangladesh. Data were collected from 120 randomly selected farmers during August 2017 with the objectives to determine the extent of the role of ICTs in increasing agricultural production. The role of ICTs was measured by Likert type rating scale with assigned score and Farmers Perception Index was used to explain the relative proportion of the statements related to perception regarding the role of ICTs. Majority of the respondents (62.50%) observed medium role of ICTs in increasing agricultural production followed by 21.67% and 15.83% observed high and low role of ICTs respectively. Correlation analysis indicated that among the selected seven socio-economic characteristics; respondent's level of education, annual family income, communication exposure, and participation in agricultural training showed positive and significant relationship with the role of ICTs. On the other hand, age, credit received and household assets showed no significant relationship with the role of ICTs in increasing agricultural production. It was found that the large portion (88.8%) of the farmers faced medium to high constraints and only 11.2% faced low constraints in using the ICTs for increasing agricultural production. South Asian J. Agric., 7(1&2): 56-60